DOES ENVIRONMENTAL PERFORMANCE DRIVE FIRM VALUE THROUGH FINANCIAL PERFORMANCE? EVIDENCE FROM INDONESIAN PROPER FIRMS - Muhammad Ilham Garnadi; Raden Lestari Garnasih (Universitas Riau, 2026)
Environmental performance is theoretically expected to increase firm value through improved financial performance; however, empirical evidence in emerging markets remains limited. This study examines whether financial performance mediates the relationship between environmental performance and firm value using panel data from Indonesian PROPER firms during 2022–2024. The population consists of 43 publicly listed PROPER firms, and the sample is selected using purposive sampling, resulting in 30 firms (90 firm-year observations). Environmental performance is proxied by emission intensity (EMISI), while financial performance is measured using Return on Assets (ROA) and Return on Equity (ROE), and firm value is measured by Tobin’s Q. The study employs panel data regression with fixed effects and follows the Baron and Kenny mediation approach.The findings show that environmental performance does not significantly affect financial performance, and thus financial performance does not mediate the relationship between environmental performance and firm value. However, financial performance, particularly ROA, has a positive effect on firm value. These results suggest that in the Indonesian emerging market context, operational efficiency remains the primary driver of firm value, while environmental performance has not yet been fully incorporated into market valuation. This finding highlights the context-dependent nature of the relationship between environmental performance and firm value and provides implications for both corporate strategy and policy design.